Anti-Inflammatory Effect of Certain Dihydroxy Flavones and the Mechanisms Involved - Vidyalakshmi, K.; Kamalakannan, P.; Viswanathan, S.; Ramaswamy, S. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2012)
This study was designed to evaluate the anti-inflammatory action of four dihydroxy flavone derivatives; 3,3'- dihydroxy flavone, 5,6-dihydroxy flavone, 3,7-dihydroxy flavone and 6,3'-dihydroxy flavone and to further investigate the multiple cellular mechanisms underlying the anti-inflammatory effect of these compounds. The effect of dihydroxy flavones on acute inflammation was studied in rats employing carrageenan induced hind paw edema method. Further, the role of proinflammatory cytokines like TNF-α and IL-1β, cyclooxygenases (COX-1 and COX-2), and free radicals in the action of flavone derivatives was investigated using in vitro assays. All the four dihydroxy flavone derivatives exhibited time and dose dependent inhibition of carrageenan induced paw edema. In addition, the investigated compounds inhibited both the isoforms of cyclooxygenase and cytokines in a concentration dependant manner and also suppressed the release of reactive oxygen species. The anti-inflammatory effect of dihydroxy flavones may be through mechanisms that involve an interaction with cyclooxygenases, cytokines and reactive oxygen species.
Keywords: reactive oxygen species